A Virtual Brain for Stereotactic Planning and Supporting Neurosurgery - Wang, Zigang; Tang, Zesheng; Wang, Tianmiao; Chen, Mengdong; Liu, Da; Tian, Zengmin (International Journal of Virtual Reality, 2000)
Visualization has becoming a powerful assistive technology for neurosurgery. This paper introduces a system for stereotactic neurosurgical planning and support. Using visualization technology the system reconstructs and displays a 3D model of the interior structure of the patient's brain. Thus the surgeons can plan for surgery using a computer model. Marker registration is used to create the mapping between the patient's head and the brain model reconstructed in the computer. During the operation a robot arm is used as a navigator to locate the pre-defined incision site and the orientation of incision route. When the robot arm locates at the pre-defined site on the patient's head, it is fixed. Various medical instruments can be installed on the tip of the robot arm. The surgeon can insert a medical instrument into the pre-defined site of the patient's head, and the surgery can be implemented successfully with the help of this system. Using a virtual environment his system can also be used to teach and train new surgeons.